Balancing struggles with desired results in everyday activities: strategies for elderly persons with physical disabilities. Issue 1 (18th July 2015) - Bontje, Peter; Asaba, Eric; Josephsson, Staffan
Abstract : The number of elderly persons with disabilities needing support with everyday activities increasing in Japan and around the world. Yet, engagement in everyday activities can support the quality of their daily life. Despite research focusing on reported meanings of people's actions, there is still limited knowledge on how engagement in everyday activity is enacted along with the meanings of persons' actions. The aim of the present study was to identify meanings of persons' actions within everyday activities of elderly Japanese with physical disabilities. Five elderly persons with physical disabilities living in the community participated in this study. Data were gathered by 10 participant observations of everyday activities supplemented with 13 unstructured interviews. Narrative analysis was used to identify meanings of persons' actions. The analysis identified an overall plot termed 'balancing struggles with desired results'. This plot illustrated that participants' and other involved individuals balanced problematic situations with finding situations that accommodated their needs. Meanings of these actions were further identified as three complementary strategies. Two of three strategies aimed to mitigate given problems, one by 'acting on a plan to achieve one's goals', the other by 'taking a step in a preferred direction by capitalising on emerging opportunities'. The third strategy focused on avoiding undesirable experiences by 'modifying problematic situations'. In conclusion, these findings call for care and rehabilitation providers' sensitivity to shifting foci of what matters in daily life's situations as well as aligning with persons' skills, resources and perspectives. Accordingly, the judicious and flexible use of these complementary strategies can enhance elderly persons' quality of daily living through everyday activities.